APPROACHES TO DEFINE THE IMPORTANCE OF TEACHER TRAINING IN UZBEKISTAN - Ranokhon Uktamboeva Hasan qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. This article provides information about the importance of teacher training, the goals and tasks of teacher training, effective methods, and pedagogical technologies used in teacher training.